Tales of… My journey into operating room nursing - Webb, Kristin (Operating Room Nurses Association of Canada Journal, 2025)
Although the Perioperative Nurse Educators of Canada (PNEC) have been around a lot longer than I have been a Clinical Educator in the Operating Room (OR), I can speak only to my memories and experience with PNEC and how I came to be its first co-chair.